Family Communication Patterns in Shaping Children’s Habits of Practising Religious Teachings - Rau Datunnisa; M. Nasor; Ade Nur Istiani (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2026)
The family serves as the foundational environment for instilling religious practices in children. This study was prompted by the increasing prevalence of digital technology use, which often distracts children from their worship routines, thus requiring adaptive parental communication strategies. The primary objective of this research is to identify and describe various family communication patterns and their specific impacts on children's religious behavior in Durian Luncuk Village, Batanghari Regency, Jambi. This study employed a qualitative field research method with a descriptive approach. Data were collected through in-depth interviews, direct observation, and documentation involving families with children aged seven to twelve years as the research subjects. The analysis followed an interactive model by Miles and Huberman involving data reduction, data display, and conclusion drawing, with data categorization conducted through open coding and axial coding, subsequently verified through source, method, and theory triangulation. The findings reveal four distinct communication typologies: authoritarian, democratic, permissive, and a blended approach. Unlike previous studies that examined a single communication pattern in isolation, this study finds that the blended approach which adaptively integrates firmness, constructive dialogue, and parental modeling is the most effective strategy in the context of digital-era challenges, constituting the primary novelty of this research. The authoritarian pattern produces fear-based obedience without genuine value internalization, while the democratic pattern fosters self-awareness through open dialogue. The permissive pattern, characterized by total freedom and lack of supervision, was found ineffective in establishing consistent religious habits. In conclusion, the quality of parental interaction is the decisive factor in shaping a child's religious character; a balanced and consistent communication style is essential for sustainable religious observance in the modern era. Practically, parents are advised to apply dialogue-based and exemplary communication, while educational institutions are encouraged to integrate family communication literacy into values-based guidance programs.